Aging of silicone rubber-based composite insulators under multi-stressed conditions: an overview. (6th September 2019) - Akbar, M; Ullah, R; Alam, S
Abstract: For over the last three decades, use of silicone rubber (SiR), in addition to the non-electrical applications, has greatly increased for high voltage electrical insulation in the outdoor environment due to its better properties particularly, high hydrophobicity. However, being organic in nature, its products are affected when exposed to multiple stresses causing loss of the desired properties having a direct bearing on their lifetime. In this review article, degradation of SiR composite insulators in the outdoor working environment due to different factors such as ultraviolet (UV) radiations, biological contaminations, water concentration or moisture absorption, tracking/erosion, partial discharges (PD), corona aging, and others are discussed. An attempt has also been made to summarize the outcome of various studies conducted aiming to retard the aging process by adding micro- and nano-sized particles of organic fillers to the base polymeric materials.